The Effect of Systemic Inflammation and Clinicopathologic Features on Survival in Malignant Pleural Mesothelioma: A Multicenter Analysis - Nadiye Sever; Sedat Yıldırım; Ali Fuat Gurbuz; Delyadil Karakaş Kılıç; Esra Zeynelgil; Yunus Emre Altintaş; Berivan Deniz Çimik; Yeşim Ağyol; Ali Kaan Güren; Pınar Erel; Erkam Kocaaslan; Burak Paçacı; et al. (Medicina)
Background and Objectives: Malignant pleural mesothelioma (MPM) is a rare and aggressive malignancy with a poor prognosis. Identifying reliable prognostic factors is crucial for risk stratification and optimizing treatment strategies. This study aimed to evaluate the impact of clinicopathologic factors and systemic inflammatory markers on survival outcomes in patients with MPM. Materials and Methods: This retrospective, multicenter study included 217 patients diagnosed with MPM between January 2009 and March 2024. Data on age, gender, histology, disease stage, treatment modalities, and inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein/albumin ratio (CAR) were collected. Survival outcomes were analyzed using Kaplan–Meier methods, and prognostic factors were evaluated using Cox regression analysis. Results: CAR was identified as an independent prognostic factor for both overall survival (OS) and progression-free survival (PFS). Patients with CAR < 0.98 had significantly longer OS (87.0 months vs. 14.0 months, p < 0.001) and PFS (17.61 months vs. 8.96 months, p = 0.010). While NLR was significant in univariate analysis (OS: 25.0 months for NLR < 2.58 vs. 21.0 months for NLR ≥ 2.58, p = 0.040), it did not retain significance in the multivariate model (p = 0.180). Epithelioid histology and early-stage disease were strongly associated with improved survival outcomes (OS: 32.0 vs. 11.0 months for epithelioid vs. non-epithelioid histology, p < 0.001; 32.0 vs. 12.0 months for early-stage vs. metastatic disease, p < 0.001). Conclusions: CAR is a strong independent prognostic factor in MPM, reflecting systemic inflammation and nutritional status. Epithelioid histology and early-stage disease are associated with significantly longer survival, underscoring the critical role of early detection in improving patient outcomes.